Idiopathic subglottic stenosis in a 32-year-old pregnant woman - Bo Toennesen; Thomas Kjærgaard; Johannes Martin Schmid (European Clinical Respiratory Journal)
Diagnosis of subglottic stenosis remains greatly a challenge for physicians due to case rarity and presentation of symptoms imitating several other more prevalent medical disorders. Idiopathic subglottic stenosis most often occurs in previously healthy perimenopausal Caucasian women. Several cases have reported symptom progression and increased stenosis, during or in between pregnancies in younger women. The following case of a 32-year-old woman provides an example of significantly long duration from initial symptom onset to diagnosis of idiopathic subglottic stenosis. Additionally, the case illustrates how pregnancy complicates diagnosis and due to the potential risk of stenosis progression and complications during labour, the patient had to undergo surgery with balloon-dilation at week 17 of pregnancy.